2020
DOI: 10.1101/2020.04.17.20064469
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness and Safety of Glucocorticoids to Treat COVID-19: A Rapid Review and Meta-Analysis

Abstract: Background: Glucocorticoids are widely used in the treatment of various pulmonary inflammatory diseases, but they are also often accompanied by significant adverse reactions. Published guidelines point out that low dose and short duration systemic glucocorticoid therapy may be considered for patients with rapidly progressing COVID-19 while the evidence is still limited. Methods:We comprehensively searched electronic databases and supplemented the screening by conducting a manual search. We included RCTs and co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 43 publications
(25 reference statements)
0
36
0
Order By: Relevance
“…However, the use of corticosteroid may non-significantly increase the risk of mortality [25]. Moreover, without reduction in mortality rate, these medications can increase duration of hospital stay [26]. The effects on mortality and outcomes can be generalized to IVIG and vitamin C in our study.…”
Section: Discussionmentioning
confidence: 79%
“…However, the use of corticosteroid may non-significantly increase the risk of mortality [25]. Moreover, without reduction in mortality rate, these medications can increase duration of hospital stay [26]. The effects on mortality and outcomes can be generalized to IVIG and vitamin C in our study.…”
Section: Discussionmentioning
confidence: 79%
“…Similar systematic review and meta‐analysis on severe acute respiratory syndrome (SARS) and the Middle East respiratory syndrome and COVID‐19 reported that systemic glucocorticoid is not beneficial for reducing the mortality (RR = 2.00, 95% CI: 0.69–5.75, I 2 = 90.9%) and the duration of lung inflammation (WMD = −1 days, 95% CI: −2.91 to 0.91) 31 …”
Section: Discussionmentioning
confidence: 92%
“…Similarly, a recent meta‐analysis have reported glucocorticoid has no role in shortening the duration of fever either in patients with severe SARS (WMD = −1.1 day, 95% CI: −4.9 to 2.7, I 2 = 58.3%) or in patients with mild SARS (WMD = 0.5 days, 95% CI: −4.2 to 5.1, I 2 = 95.1%) 31 …”
Section: Discussionmentioning
confidence: 93%
“…A third study 242 that used the second week pulsing of low‐dose methylprednisolone noted that this was effective in improving the prognosis of patients with severe COVID‐19 pneumonia. Several reviews 243,244 of the use of corticosteroids in COVID‐19 found that in adults with COVID‐19, the use of systemic glucocorticoids did not reduce mortality and prolonged the duration of hospitalization. Two factors are likely to have influenced these seemingly conflicting results.…”
Section: Therapy Of Sars‐cov‐2 Infections Based On the Pathogenesis Omentioning
confidence: 99%
“…However, the use of antiviral agents will depend on the targeted mechanism 22 and should be done early in the COVID‐19 infection before the host hyperinflammatory reaction occurs 214 . Reviews of antiviral options and the theoretical reasons for their use in the therapy of COVID‐19 have been published 241–245 . In the following sections, only those antiviral agents that have demonstrated reasonable efficacy in COVID‐19 patients will be reviewed in detail.…”
Section: Therapy Of Sars‐cov‐2 Infections Based On the Pathogenesis Omentioning
confidence: 99%